Laparoscopic laser lithotripsy inside the endocatch bag: An alternative technique for removal of large post lap pyelolithotomy calculi - Sandhu, Jaspreet Singh (Med J Armed Forces India, 2018)
Large staghorn calculi in unascended pelvic kidneys and in normally located kidneys with anatomy unsuitable for percutaneous nephrolithotomy have to be treated via pyelolithotomy. When performed laparoscopically, the extraction of these staghorn calculi, without extending skin incision at the port site is challenging. We describe the successful use of laparoscopic laser lithotripsy, intracorporeally, with the entrapped calculus inside the endocatch bag, for fragmentation and retrieval without extension of skin incision.